2016
DOI: 10.1080/17469899.2016.1203254
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of corneal infections

Abstract: Introduction Ocular infections remain an important cause of blindness worldwide and represent a challenging public health concern. In this regard, microbial keratitis due to fungal, bacterial, or viral infection can result in significant vision loss secondary to corneal scarring or surface irregularity. Left untreated corneal perforation and endophthalmitis can result, leading to loss of the eye. Rigorously studied animal models of disease pathogenesis have provided novel information that suggests new modes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 111 publications
1
26
0
Order By: Relevance
“…(31) The most common risk factors for bacterial keratitis include ocular trauma, surgery, concurrent ocular surface disease, immunosuppression and the use of contact lenses. (7,32) Similar to other bacterial infections, the pathogenesis of bacterial keratitis (caused primarily by extracellular bacteria) is dependent on the species of the bacteria, the virulence factors and host immune response. (33) Heimer et al (Table 1) investigated the gene expression of human corneal epithelial cells secondary to infection with Staphylococcus aureus.…”
Section: Bacterialmentioning
confidence: 99%
See 2 more Smart Citations
“…(31) The most common risk factors for bacterial keratitis include ocular trauma, surgery, concurrent ocular surface disease, immunosuppression and the use of contact lenses. (7,32) Similar to other bacterial infections, the pathogenesis of bacterial keratitis (caused primarily by extracellular bacteria) is dependent on the species of the bacteria, the virulence factors and host immune response. (33) Heimer et al (Table 1) investigated the gene expression of human corneal epithelial cells secondary to infection with Staphylococcus aureus.…”
Section: Bacterialmentioning
confidence: 99%
“…(38,39) Infiltration of innate immune cells and upregulation of pro-inflammatory, chemotactic, and regulatory cytokines is the vigorous immune response that patients with keratitis mount to Aspergillus and Fusarium hyphae formation. (7) Studies have shown that individuals with a compromised IL-17 response, primarily as a results of autoantibodies against IL-17, are more vulnerable to yeast fungal infections, particularly candidiasis at mucosal surfaces. (40,41) Other studies have shown that mutations in the STAT3 gene, which is required for the production of IL-17, increase the susceptibility of individuals to infections with Candida.…”
Section: Bacterialmentioning
confidence: 99%
See 1 more Smart Citation
“…6D) at 5 days p.i. Next, we used a 32-plex bead-based protein assay to determine whether the expression of inflammatory mediators both known and unknown to ocular HSV-1 had altered expression in this model (16). Surprisingly, no change was found in analyte expression between the corneas of mice with and without HGs at 5 days p.i.…”
mentioning
confidence: 99%
“…In 2010, the Centers for Disease Control and Prevention reported that 700,000 clinical visits occurred due to microbial infections of the cornea, or microbial keratitis, in the United States (14). Depending on the pathogen, tissue pathology can occur by direct cytopathic effects (e.g., virus), secreted toxins (e.g., bacteria), or immunemediated damage that can result in opacity and scar formation of the cornea (15,16). Host clearance of the insulting pathogen can also lead to corneal neovascularization (comprised of blood and lymphatic vessel formation), as in cases of herpes simplex virus 1 (HSV-1) keratitis (15).…”
mentioning
confidence: 99%